Inhibition of Spinal Microglia and Astrocytes Contributes to the Anti-Allodynic Effect of Electroacupuncture in Neuropathic Pain Induced by Spinal Nerve Ligation. Issue 1 (February 2016) - Liang, Yi; Qiu, Yujie; Du, Junying; Liu, Jin; Fang, Junfan; Zhu, Ji; Fang, Jianqiao
Objective: Besides neurons, activated microglia and astrocytes in the spinal cord dorsal horn (SCDH) contribute to the pathogenesis of chronic pain. Electroacupuncture (EA) has been used widely to treat various chronic pain diseases, however, the underlying mechanisms of EA are still not fully understood. Methods: Male Sprague-Dawley rats were randomly divided into four groups, including an untreated healthy Control group (n=14), a True-spinal nerve ligation (SNL) group that underwent SNL and remained untreated (n=25), a True-SNL+EA group that underwent SNL followed by EA treatment (n=25), and a Sham-SNL group that underwent sham surgery and remained untreated (n=15). SNL was performed unilaterally at L5 and EA was applied to ST36 and BL60 bilaterally once per day. Paw withdrawal thresholds (PWTs) were measured ipsilaterally at baseline and 1, 3, 7, and 14 days after ligation. Activation of microglia and astrocytes in the SCDH were examined bilaterally by immunofluorescence staining, and concentrations of interleukin-1β (IL-1β) and interleukin (IL-6) were measured in the ipsilateral SCDH by ELISA. Results: SNL significantly decreased PWTs and activated glial cells in the superficial laminae of the ipsilateral SCDH. In rats with SNL, glial fibrillary acidic protein (GFAP) immunoreactivity peaked at 7 days and was maintained until 14 days post-ligation, while anti-integrin alphaM (OX-42) immunoreactivity peaked at 3 days and declined gradually. EA significantly alleviated SNL-induced mechanical allodynia. Furthermore, EA reduced microglial activation (OX-42 positive ratios) in the lumbar SCDH at 3 days post-ligation and suppressed astrocyte activation (GFAP positive ratios) at all time points observed. Conclusions: EA stimulation alleviates SNL-induced neuropathic pain, at least in part through inhibition of spinal glial activation. Moreover, inhibition of spinal microglia and astrocyte activation may contribute to the immediate effects and maintenance of EA analgesia, respectively.